PP.37.28: SNORING BUT NOT SLEEPINESS IS RELATED TO AORTIC ROOT DIAMETER IN HYPERTENSIVE PATIENTS. RESULTS FROM THE SLEEPART STUDY. (June 2015) - Baguet, J.-P.; Courand, P.Y.; Lequeux, B.; Delsart, P.; Barber-Chamoux, N.; Sosner, P.; Baguet, S.; Lopes-Sublet, M.L.
Abstract : Objective: Obstructive sleep apnea (OSA) has been recently implied in the genesis of a dilatation of the ascending aorta. Snoring and sleepiness are both frequent symptoms occurring in OSA. To date, no data are available concerning a potential relationship between snoring or excessive daytime sleepiness on the one hand and increased aortic root diameter on the other hand. Design and method: 169 hypertensive patients, without treated OSA nor known thoracic aortic disease, were included in 6 tertiary hypertension (HTN) centers. They received questionnaires about snoring (Epworth's scale) and sleepiness, and had clinical examination, biology and cardiac ultrasound (measurement of aortic root diameter at the level of the Valsalva's sinuses). Results: Main characteristics were as follows (mean): age 54.6 + 12.9 years, 115 men (68%), BMI 28.9 + 5.2 kg/m 2, clinic blood pressure 150 + 20/91 + 13 mmHg. 125 patients (74%) were treated for HTN (2.54 + 1.38 antihypertensive drugs per patient). Mean Epworth's score was 6.2 + 4.5, 74 subjects (44%) notified snoring (often or always), 28 (17%) were sleepy, mean Valsalva's sinuses aortic diameter was 33.1 + 4.4 mm. Aortic diameter was correlated to weight, height, serum creatinine, HDL cholesterol, triglycerides and number of antihypertensive drugs, and was higher in men (34.5 + 4.3 vs. 30.2 + 3.0 mm, p < 0.001). Only height was independently linked to aortic diameter (p < 0.01). Aortic root diameter was similar in sleepy and not sleepy patients. Snorers had a significantly higher aortic diameter (34.1 + 4.5 vs. 32.2 + 4.3 mm, p = 0.012), even after indexation by height (p = 0.047) and a worse metabolic profile than patients without significant snoring. Conclusions: Snoring, but not excessive daytime sleepiness, was associated with an increased aortic root diameter during hypertension. On account of that, its detection should be included in the usual questionnaire of hypertensive patients. The relationship between snoring and increased aortic diameter is mainly due to the presence of OSA, in which snoring occurs more frequently than excessive daytime sleepiness.